Respuesta :
y = 6x^2 + 10x - 4
= 6x^2 + 12x - 2x - 4
= 6x(x + 2) - 2(x + 2)
= (6x - 2)(x + 2)
X intercepts are: -2 and 1/3
it is D
= 6x^2 + 12x - 2x - 4
= 6x(x + 2) - 2(x + 2)
= (6x - 2)(x + 2)
X intercepts are: -2 and 1/3
it is D
x intercpe is when y=0
0=6x^2+10x-4
factor
0=2(3x^2+5x-2)
assume
0=3x^2+5x-2
0=(x+2)(3x-1)
set to zero
x+2=0
x=-2
3x-1=0
x=1/3
x intercepts are -2 and 1/3
D is answere
0=6x^2+10x-4
factor
0=2(3x^2+5x-2)
assume
0=3x^2+5x-2
0=(x+2)(3x-1)
set to zero
x+2=0
x=-2
3x-1=0
x=1/3
x intercepts are -2 and 1/3
D is answere